2017
DOI: 10.1007/s00238-017-1306-y
|View full text |Cite
|
Sign up to set email alerts
|

A new treatment for reliable functional and esthetic outcome after local facial flap reconstruction: a transparent polycarbonate facial mask with silicone sheeting

Abstract: BackgroundFacial flap surgery predominantly leads to good functional results. However, in some cases, it can cause unsatisfactory esthetic results. They include persistent erythema, pincushioning, and development of hypertrophic scars. Conservative, reliable treatment for facial flaps is lacking. Pressure and silicone therapy have proven to result in significant improvement in scar erythema, pliability, and thickness in postburn hypertrophic scars. By combining these therapies in a facial mask, the esthetic ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Surface area demonstrated a statistically significant improvement between start and end of therapy in the Patient Scale of the POSAS in patients with hypertrophic scars and protruding flaps after facial flap surgery. 14 Furthermore, this study reported a statistically significant improvement in scar itchiness, pigmentation, pliability, and thickness. Concerning the Observer Scale, thickness, pliability, and surface area improved significantly.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Surface area demonstrated a statistically significant improvement between start and end of therapy in the Patient Scale of the POSAS in patients with hypertrophic scars and protruding flaps after facial flap surgery. 14 Furthermore, this study reported a statistically significant improvement in scar itchiness, pigmentation, pliability, and thickness. Concerning the Observer Scale, thickness, pliability, and surface area improved significantly.…”
Section: Resultsmentioning
confidence: 56%
“…The included articles originated from China (two) and the Netherlands (one) and were published in 2016 and 2017. Two articles described patients with hypertrophic scars caused by thermal or chemical burns 12,13 and one study 14 included patients with hypertrophic scars and protruding skin flaps after facial flap surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This therapy has recently proven to be effective as an adjuvant therapy for treating unaesthetic results after facial flap surgery. 21 In this article, the fabrication process of this facial mask is put apart. The study was approved by the local ethics committee of the MUMC+.…”
Section: Aimmentioning
confidence: 99%
“…Treatment with such a mask results in a reduction of flap thickness and scar erythema, improvement of skin irregularities, and pliability of the skin. 8 However, from a psychological point of view, the impact of wearing a full-face pressure mask is not well documented.…”
mentioning
confidence: 99%